2016
DOI: 10.3390/en9121079
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Models for Viscoelastic Liquid Atomization Spray

Abstract: Atomization spray of non-Newtonian liquid plays a pivotal role in various engineering applications, especially for the energy utilization. To operate spray systems efficiently and well understand the effects of liquid rheological properties on the whole spray process, a comprehensive model using Euler-Lagrangian approaches was established to simulate the evolution of the atomization spray for viscoelastic liquid. Based on the Oldroyd model, the viscoelastic linear dispersion relation was introduced into the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The electrospinning of polyisobutylene-based solutions was investigated theoretically by Carroll and Joo 46 and numerically using the FENE-P model by Zhmayev et al 47 . Additionally, the atomization of polymer solutions was numerically modeled by Qian et al 48 . Li et al 49 used Oldroyd-B and leaky dielectric models to investigate viscoelastic jet axisymmetric and nonaxisymmetric instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The electrospinning of polyisobutylene-based solutions was investigated theoretically by Carroll and Joo 46 and numerically using the FENE-P model by Zhmayev et al 47 . Additionally, the atomization of polymer solutions was numerically modeled by Qian et al 48 . Li et al 49 used Oldroyd-B and leaky dielectric models to investigate viscoelastic jet axisymmetric and nonaxisymmetric instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the viscoelastic properties of the non-Newtonian PIB kerosene, the cooling film disintegration slowed down and the wavelength of the sheet increased. This resulted in higher travelling distance of the undistorted liquid sheet [3,19].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of the primary breakup have gained lots of interest and have been investigated in detail by many researchers. Through experimental exploration and numerical simulations, the primary breakup process of Newtonian fluids is governed by air–liquid interface instabilities. Many factors affect the performance of primary breakup, such as injection pressure, nozzle geometry, and liquid properties. To describe the magnitude of surface tension and aerodynamic force, Weber proposed a dimensionless number We = ρ g ( u g – u l ) 2 D l /σ, where ρ g is the air density, u g is the air velocity, u l is the liquid velocity, D l is the exit diameter of the liquid jet, and σ is the surface tension. The viscosity of the working liquid also influences the primary breakup process. , Another important dimensionless number is the ratio of gas-to-liquid momentum flux M = ρ g u g 2 /ρ l u l 2 , proposed by Leroux et al, where ρ l is the density of the liquid jet.…”
Section: Introductionmentioning
confidence: 99%
“…39−41 Experimental results showed that viscoelasticity influences the evolution and distribution of the drops at the far field. 23,42 Through experimental and simulation studies, it is indicated that the shear-thinning behavior enhances the breakup of the jet. 43−45 According to Ertl and Weigand, 46 the external surface of the jet deforms due to the high-velocity gradient, which leads to a decrease in viscosity and allows it to deform more easily.…”
Section: Introductionmentioning
confidence: 99%